2008
DOI: 10.3928/01484834-20081001-07
|View full text |Cite
|
Sign up to set email alerts
|

Role Transition During RN-to-FNP Education

Abstract: This study examines the role transition that occurs during RN-to-family nurse practitioner (FNP) education, described in an earlier qualitative study that identified a role transition framework of influential positive forces and obstacles. The purposes of the study were to validate the educational phase of the original framework and explore other role transition issues. The study used a descriptive correlational design by asking all FNPs in two rural western states to participate by answering a questionnaire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…For example, previous NP-focused research highlights the importance of RN experience and suggests that it is beneficial to NP role transition. 1,3,28 However, studies have reported that new NPs found NP clinical experience to be beneficial during role transition. 8,9 This finding adds to the body of NP role transition research and may be of use in informing and helping to frame the discussion on providing the appropriate experiences to NPs.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…For example, previous NP-focused research highlights the importance of RN experience and suggests that it is beneficial to NP role transition. 1,3,28 However, studies have reported that new NPs found NP clinical experience to be beneficial during role transition. 8,9 This finding adds to the body of NP role transition research and may be of use in informing and helping to frame the discussion on providing the appropriate experiences to NPs.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The majority of NPs who reflected on their educational experiences felt only somewhat or minimally prepared in clinical skills after completing their basic NP education (Cusson & Strange, 2008;Hart & MacNee, 2007;Kelly & Mathews, 2001;Rosenzweig et al, 2012;Sargent & Olmedo, 2013;Steiner, McLaughlin, Hyde, Brown, & Burman, 2008). While there is scarce literature on the impact of educational background on transitioning to the first PC NP role, researchers have found no significant difference in academic performance between traditional and nontraditional (non-nurse college graduate [NNCG]) master's students in their educational NP programs (Munro & Krauss, 1985;Sime, Corcoran, & Libera, 1983;Smith & Shoffner, 1991).…”
Section: Individual Characteristics Of the Npmentioning
confidence: 99%
“…However, Rich (2005) found no correlation between duration of prior RN experience and level of competency in NP clinical skills as determined by NP self-report, but physicians working with the NPs rated those with fewer years of RN experience as having greater competency in clinical skills than those with more years of RN experience. More recent studies have shown mixed results, as more RN experience led to improved adaption to the NP role (Cusson & Strange, 2008;Kelly & Mathews, 2001), while others validated the lack of correlation between prior RN experience and NP role transition (Barnes, 2015;Steiner et al, 2008).…”
Section: Prior Work Experiencementioning
confidence: 99%
“…APN students have the responsibility of acquiring new knowledge and skills, as well as learning to use their previous nursing knowledge in a new way (Cragg & Andrusyszyn, 2005;Griffith, 2004;Heitz, Steiner, & Burman, 2004). APN education is a time of change, with RNs struggling to learn and practice in a different nursing role (Manning & Neville, 2009;Steiner, McLaughlin, Hyde, Brown, & Burman, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%